COVID-19 risk perception and tourist satisfaction: A mixed-method study of the roles of destination image and self-protection behavior - Zhou, Bin; Liu, Si-yi; Wang, Ling-en; Wang, Lu-ting; Wang, Yu-xin (Frontiers in Psychology, 2022)
This study aimed to examine the effects of COVID-19 risk perception on negative destination image and self-protection behavior, and the resultant effects on tourist satisfaction. Hence, this study applied a continuous interpretive mixed-method design combining quantitative and qualitative analyses. A quantitative survey (n = 486) in the cities of Ningbo, Huangshan, and Chengdu, China, and 19 qualitative interviews were conducted online. The results of the quantitative study show that: (1) Risk perception and negative destination image are antecedent variables influencing tourist satisfaction, and (2) there are significant positive correlations between risk perception and negative destination image, risk perception and tourist self-protection behavior, and negative destination image and tourist self-protection behavior. Moreover, (3) negative destination image had a partial mediating effect between risk perception and satisfaction. Furthermore, to supplement the research data and expand the quantitative findings, this study further examined whether the above variables are related to tourist satisfaction, through in-depth interviews with tourists. The findings showed that COVID-19 risk perception, negative destination image, and self-protection behavior all affect tourist satisfaction. The findings provide valuable crisis management suggestions for the government and should contribute to the efforts of tourist destinations to build a healthy and safe image, thereby contributing to the sustainable development of tourism industries in the post-epidemic era.